Multicentric Castleman's disease in a Ghanaian adult. - Dei-Adomakoh, Y.A.; Segbefia, C.; Ekem, I.; Taylor, A. (Ghana medical journal, 2013)
Castleman's disease is a rare cause of lymphoid hyperplasia that may result in localized symptoms or an aggressive, multisystem disorder that can mimic other diseases like lymphoma or tuberculosis. We describe a case of a 55-year-old Ghanaian male who was successfully diagnosed and managed for multicentric Castleman's disease with combination chemotherapy.
Keywords: Castleman's disease; lymphoid hyperplasia; multisystem disorder; tuberculosis; chemotherapy